2021
DOI: 10.1101/2021.01.02.21249146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do school closures and school reopenings affect community transmission of COVID-19? A systematic review of observational studies

Abstract: IntroductionSchool closures are associated with significant negative consequences and may exacerbate inequalities. They were implemented worldwide to control SARS-CoV-2 in the first half of 2020, but their effectiveness remains uncertain. This review summarises the empirical evidence of their effect on SARS-CoV-2 community transmission.MethodsThe study protocol was registered on Prospero (ID:CRD42020213699). On 12 October 2020 we searched PubMed, Web of Science, Scopus, CINAHL, the WHO Global COVID-19 Research… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 63 publications
(455 reference statements)
0
27
0
2
Order By: Relevance
“…As the epidemiological situation has improved, reopening schools has become imperative. Walsh et al 59 found that there is no increase in community transmission of COVID-19 after reopening schools in a low transmission context with appropriate mitigation measures, as it was observed in Norway and Denmark 66 . However, in countries like Germany, that reopened schools when community transmission was still high, it can lead to an increase in the growth rate 66 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As the epidemiological situation has improved, reopening schools has become imperative. Walsh et al 59 found that there is no increase in community transmission of COVID-19 after reopening schools in a low transmission context with appropriate mitigation measures, as it was observed in Norway and Denmark 66 . However, in countries like Germany, that reopened schools when community transmission was still high, it can lead to an increase in the growth rate 66 .…”
Section: Discussionmentioning
confidence: 94%
“…They found that the effect of school closures was comparatively lower than other measures. In a recent systematic review of observational studies analysing school closing and reopening Walsh et al 59 found that half of the studies with lower risk of bias concluded that school closing reduced community transmission while half of the studies found no effect. Other analyses 60 , 61 , 62 , 63 , 64 , 65 suggest that school closingmay have been a more important factor during the first wave of the COVID-19 epidemic than initially thought.…”
Section: Discussionmentioning
confidence: 99%
“…In observational US data from early 2020, school closure was associated with significant declines in COVID-19 incidence and mortality, 25 whereas in systematic review of observational studies, effects of school closure are inconsistent. 8 Several modelling studies - usually from the first wave of the pandemic - suggest modest to substantial associations between school closures and incidence. 5,26 These include estimates of 40-60% reduced peak incidence, 26 and of reducing the reproduction number by more than a third.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Observational studies on the association of school closures with community transmission have yielded inconsistent results, ranging from none to substantial reduction. 8 When considering infection risks, a distinction needs to be made between schools, students and age-typical, contextual whereabouts, e.g., public transport or after-school meetings. Limited data suggest that schools are not high-risk settings for SARS-CoV-2 transmission between students and/or staff.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they do not account for indirect effects of school closures which prevent parents from working outside the home. A systematic review26 of observational studies showed that in those studies with lowest risk of bias, school closures had no discernible effect on SARS-CoV-2 transmission.…”
Section: Transmissionmentioning
confidence: 99%